Investigating the Uptake and Fate of Poly- and Perfluoroalkylated Substances (PFAS) in Sea Ice Using an Experimental Sea Ice Chamber - Jack Garnett (6802640); Crispin Halsall (1862722); Max Thomas (5587202); Odile Crabeck (10916971); James France (836552); Hanna Joerss (649633); Ralf Ebinghaus (1462171); Jan Kaiser (2510149); Amber Leeson (6802646); Peter M. Wynn (2389882) (2021)
Poly- and perfluoroalkyl substances (PFAS) are contaminants of emerging Arctic concern and are present in the marine environments of the polar regions. Their input to and fate within the marine cryosphere are poorly understood. We conducted a series of laboratory experiments to investigate the uptake, distribution, and release of 10 PFAS of varying carbon chain length (C 4 –C 12 ) in young sea ice grown from artificial seawater (NaClsolution). We show that PFAS are incorporated into bulk sea ice during ice formation and regression analyses for individual PFAS concentrations in bulk sea ice were linearly related to salinity ( r 2 = 0.30 to 0.88, n = 18, p < 0.05). This shows that their distribution is strongly governed by the presence and dynamics of brine (high salinity water) within the sea ice. Furthermore, long-chain PFAS (C 8 –C 12 ), were enriched in bulk ice up to 3-fold more than short-chain PFAS (C 4 –C 7 ) and NaCl. This suggests that chemical partitioning of PFAS between the different phases of sea ice also plays a role in their uptake during its formation. During sea ice melt, initial meltwater fractions were highly saline and predominantly contained short-chain PFAS, whereas the later, fresher meltwater fractions predominantly contained long-chain PFAS. Our results demonstrate that in highly saline parts of sea ice (near the upper and lower interfaces and in brine channels) significant chemical enrichment (ε) of PFAS can occur with concentrations in brine channels greatly exceeding those in seawater from which it forms (e.g., for PFOA, ε brine = 10 ± 4). This observation has implications for biological exposure to PFAS present in brine channels, a common feature of first-year sea ice which is the dominant ice type in a warming Arctic.